POLEMIK IMPLEMENTASI PEMBERIAN HAK RESTITUSI DALAM TPPO: PERDAGANGAN ORANG ATAU PEKERJA MIGRAN ILEGAL? - Siahaan, Hervyan; Sudirman, Lu; Girsang, Junimart (Universitas Muhammadiyah Ponorogo, 2023)
Fulfilling justice for trafficking victims is not enough to be imprisoned alone but must come to the recovery of the suffering losses of trafficking victims. In Law Number 21 of 2007 concerning the Eradication of Trafficking in Persons, it stipulates the rights that can be given to victims, one of which is the right to restitution that must be given by traffickers as compensation to victims, in this case based on District Court Decision Number: 109 / Pid.Sus / 2022 / PN Tp, the defendant was convicted in accordance with the second alternative charge JPU Article 81 Jo Article 69 of Law of the Republic of Indonesia Number 18 of 2017 concerning the Protection of Migrant Workers as amended by Law of the Republic of Indonesia Number 11 of 2020 concerning Job Creation Jo Article 55 paragraph (1) to – 1 of the Penal Code with a prison sentence of 10 (ten) years and a fine of IDR 1,000,000,000 (one billion rupiah). The method used in this study is normative-empirical legal research by examining actual actions in the form of legal documents (judges' decisions) which are then adjusted to applicable rules and regulations, information collected through online literature searches, books, and related regulations. In this legal research, legal approaches, conceptual approaches, and case approaches will be used, along with specific research needs. In this study, primary and secondary legal materials were used. The legal material analyzed is presented methodically, logically, and reasonably. Based on the findings of the study, it can be concluded that the conviction in the judgment number 109/Pid.Sus/2022/PN Tp by being convicted of legally and convincingly violating the articles contained in the PMI Law, justice for victims is not fulfilled where the type of crime is a criminal offense that is not included in the provisions of article 2 paragraph (1) letter a of Perma Number 1 of 2022.